MENINGKATKAN HASIL BELAJAR DASAR AKUNTANSI SISWA SMK MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) BERBASIS PENDEKATAN DEEP LEARNING - Muhammad Rofi'uddin; Mardi; Khansha Sindra Irfani; Neneng Murni (Qalam : Jurnal Ilmu Kependidikan, 2026)
This study aims to improve learning outcomes in Basic Accounting, particularly in the Adjustment Journal material, through a cooperative learning model of the Teams Games Tournament (TGT) type based on the Deep Learning approach. The main problem of the study is the low learning outcomes of students due to the lack of varied learning methods. The method used is Classroom Action Research (CAR) which was implemented in two cycles. The subjects of the study were grade 10 students. Data were collected through student learning achievement tests, then analyzed descriptively and comparatively. The results of the study concluded that there was a significant increase in student learning completeness, namely from 52.8% in Cycle I to 86.1% in Cycle II. This increase indicates that the combination of the TGT model and the Deep Learning approach is effective in increasing students' in-depth understanding and activeness. In conclusion, this model can be implemented as an innovative solution to optimize accounting learning outcomes in vocational schools.